HUBUNGAN BEBAN KERJA DAN TINGKAT STRES SELAMA PANDEMI COVID-19 DENGAN BURNOUT SYNDROME PADA PERAWAT DI RUMAH SAKIT RUJUKAN COVID-19 RSUD PASAR REBO TAHUN 2021 - Eti Wiyati Nurcahyani (2021)
During the covid-19 pandemic, nurses are faced with many tasks and direct exposure to Covid-19 positive patients. High workloads and stress levels of nurses, can lead to burnout syndrome. That will have an impact on work productivity and the quality of medical care. Therefore, this study aims to find out the relationship of workload and stress level with burnout syndrome on nurses in Pasar Rebo General Hospital. The design of the study used quantitative analytic observational with a cross-sectional approach. The total samples of the study were 85 nurses of Pasar Rebo General Hospital with a purposive sampling technique. The data were obtained by filling out questionnaires online via google form in July 2021. The data analysis used the chi-square test with significance value of < 0,05. The results of the study showed 58.8% of nurses with a heavy workload, 57.6% of nurses with a mild stress level, and 62.4% of nurses with mild burnout syndrome. The significant relationship of workload (p-value = 0.002) and stress level (p-value = 0.000) with burnout syndrome on nurses was obtained. Suggestions for research institutions are increasing the number of nurses, the implementation of the community intervention program and the implementation of stress management training.